2002
DOI: 10.1079/joh200297
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites of three species of house geckoes in Lampung, Indonesia

Abstract: Thirty-four house geckoes (21 Cosymbotus platyurus, four Gehyra mutilata and nine Hemidactylus frenatus) in December, 1997 (rainy season) and 26 geckos (16 C. platyurus, six G. mutilata and four H. frenatus) in July, 2000 (dry season) were captured in Lampung, Indonesia. Some species of geckoes have been inadvertently introduced to many tropical regions from their native region, but the three species of geckoes in this study are native to Indonesia. Six species of endoparasites were recovered: Oochoristica jav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…If we assume that pentastomes have a similar pre-patent period in toads as they do in their usual gecko host (>240 days), the high prevalence in the build-up implies that peak transmission occurs from mid-wet season to mid-build-down (Jan–Apr). The prevalence and intensity of R. frenatus in 3 lizard species ( Cosymbotus platyurus , Gehyra mutilata and H. frenatus ) from Indonesia (Matsuo and Oku, 2002) show comparable mean values to our own data, but do not reveal any seasonal variation. However, the Indonesian data are difficult to interpret because they are based on a single wet season and a single dry season sampled 3 years apart.…”
Section: Discussionsupporting
confidence: 76%
“…If we assume that pentastomes have a similar pre-patent period in toads as they do in their usual gecko host (>240 days), the high prevalence in the build-up implies that peak transmission occurs from mid-wet season to mid-build-down (Jan–Apr). The prevalence and intensity of R. frenatus in 3 lizard species ( Cosymbotus platyurus , Gehyra mutilata and H. frenatus ) from Indonesia (Matsuo and Oku, 2002) show comparable mean values to our own data, but do not reveal any seasonal variation. However, the Indonesian data are difficult to interpret because they are based on a single wet season and a single dry season sampled 3 years apart.…”
Section: Discussionsupporting
confidence: 76%
“…The overall prevalence (45.9%) of pentastomids infecting the studied population of H. mabouia was markedly lower than those reported for H. mabouia from Puerto Rico (89%; Simonsen and Sarda, 1985) and for H. haitianus from the Caribbean Hispaniola Island (62%; Powell et al, 1993), but they were higher than H. turcicus from the United States (19.8%; Riley et al, 1988) and H. frenatus from Indonesia (25-33%; Matsuo and Oku, 2002). In Brazil, the studies have shown unequal prevalence in native lizards species Mabuya agilis (3.6-9.0%; Vrcibradic et al, 2002); Cnemidophorus abaetensis (6.0%; Dias et al, 2005), and C. ocellifer (2.5%; Dias et al, 2005); and Tropidurus hispidus (11.1%; Almeida et al, 2008).…”
Section: Discussionmentioning
confidence: 57%
“…Eggs of S. brevicaudata are thick-shelled, containing embryos at deposition (Yamaguti 1961). in one study, the prevalence of a nematode, Spauligodon hemidactylus was significantly higher in the rainy season than in the dry season (Matsuo and Oku 2002). There were no monthly differences in the prevalence or intensity of infection in adults examined by Amo et al (2005).…”
Section: Discussionmentioning
confidence: 91%